ANGII Initiated HSF2 Trans‐Activating HIF ‐1α Through Induction of ER Stress to Promote Cardiac Hypertrophy - Renchuang Cao; Qingying Meng; Gengyuan Li; Shumei Yuan; Chunmei Li; Xin Zhao; Dongmei Zhang (Clinical and Experimental Pharmacology and Physiology, 2026)
ABSTRACT Heat shock factor 2 (HSF2) and hypoxia‐inducible factor 1α are activated by angiotensin II (ANGII) in cardiomyocytes. The endoplasmic reticulum (ER) stress plays a critical role in cardiac hypertrophy. Moreover, HIF‐1α is known to be regulated by HSF2 in tumour cells. In this study, we hypothesised and clarified whether HSF2 trans‐activated HIF‐1α through initiation of ER stress in hypertrophic cardiomyocytes. Myocardial hypertrophy was induced by the treatment of ANGII. Expression of the gene or protein was assessed by applying RT‐PCR, WB, ICC and IHC. Luciferase and CHIP were applied to detect the transcription of HIF‐1α by HSF2. Both in vitro and in vivo, the expression of HIF‐1α, ER stress markers and HSF2 was increased in ANGII‐treated hypertrophic cardiomyocytes. Blocking ER stress suppressed the expression of HSF2 and HIF‐1α in ANGII‐treated cardiomyocytes. Silencing HSF2 inhibited HIF‐1α, thereby reducing hypertrophy but had no effect on ER stress. Similarly, silencing HIF‐1α reduced hypertrophy without affecting ER stress or HSF2 expression. HSF2 transcriptionally activated HIF‐1α. We concluded that ER stress induced by ANGII activates HSF2, which then trans‐activates HIF‐1α, promoting cardiac hypertrophy.